Analysis of RNFL Thickness among Different Refractive States Using OCT - Muhammad Ijaz Ahmad, Safa Omer Wd Haj Hamed, Nuha Mohamed Fat Manzoor Ahmad Qureshi, Abd Elaziz Mohame (Pakistan Journal of Ophthalmology, 2019)
Purpose: To measure the retinal nerve fiber layer (RNFL) thickness in myopic and hyperopic eyes and to compare it with emmetropic control eyes by Optical Coherence Tomography. Study Design: Cross sectional comparative study. Place and Duration of Study: Done in Makka eye complex Alkalakla, Sudan, from May to November 2017. Material and Methods: In this study 150 participants (300 eyes) of myopia, hypermetropia and emmetropia were recruited and arranged in three groups having 50 cases each. Myopia and hypermetropia greater than 2.00 D, and emmetropia (+0.50 to -0.50 D) were recruited. The participants were 15-30 years old and they were free from ocular disease and had not undergone any surgery. Objective refraction by auto refractor and corrected visual acuity by snellen projector chart was checked. RNFL Thickness was measured by OCT. Results: The nerve fiber layer thickness mean in myopic (92.32 ) group was significantly different from hyperopic (102.12 ) and emmetropic (98.80 ) groups. After applying ANOVA test the difference between the Myopes against Hypermetropes, and myopes against emmetropes were found statistically significant (p < 0.05) as compared to hypermetropes against emmetropes (p = 0.152). The mean values of RNFL thickness were thinner in nasal, temporal, superior and inferior in myopes than hypermetropes and were statistically significant (p < 0.05). But the mean value of RNFL thickness of temporal and superior part was thicker in emmetropes than hypermetropes. Conclusion: The RNFL thickness was found thinner in myopic participants as compared to hyperopic and emmetropics. Keywords: Retinal nerve fiber layer, Optical Coherence Tomography, Refractive error.